Analyzing the Impact of Electric Vehicles on the Power Network of the United Arab Emirates - Suma Al-Arab; Ramesh C. Bansal; Ahmed G. Abo-Khalil (International Transactions on Electrical Energy Systems)
This study investigates the impact of increasing electric vehicle (EV) adoption on the power grid in the United Arab Emirates (UAE), focusing on grid performance, stability, and efficiency under different EV penetration scenarios. A mathematical model is developed to evaluate EV charging load profiles based on energy consumption, charging schedules, and station distribution. The results reveal that level 1 (120 V) charging stations generate a peak load of 93.6 kW, whereas level 2 (240 V) stations impose a significantly higher peak load of 187.2 kW. The study finds that while the existing power grid can support up to 40% EV penetration with level 1 charging, it risks exceeding capacity with level 2 infrastructure. By 2030, a 40% EV penetration with level 2 charging is projected to surpass the system’s margin capacity, increasing the likelihood of voltage instability and transformer overloads. This research is novel in its UAE-specific modeling of EV charging impacts, offering detailed insights into grid constraints under future EV growth. To mitigate these challenges, the study recommends dynamic pricing strategies and vehicle-to-grid (V2G) technology to optimize load distribution and enhance grid resilience. The findings provide essential guidance for policymakers, utilities, and industry stakeholders in developing a sustainable and efficient EV charging infrastructure.